Synthesis, Physicochemical Characterization, In Vitro 2D/3D Human Cell Culture, and In Vitro Aerosol Dispersion Performance of Advanced Spray Dried and Co-Spray Dried Angiotensin (1-7) Peptide and PNA5 with Trehalose as Microparticles/Nanoparticles for Targeted Respiratory Delivery as Dry Powder Inhalers - Wafaa Alabsi; Maria F. Acosta; Fahad A. Al-Obeidi; Meredith Hay; Robin Polt; Heidi M. Mansour (MDPI AG, 2021)
The peptide hormone Angiotensin (1-7), Ang (1-7) or (Asp-Arg-Val-Tyr-Ile-His-Pro), is an essential component of the renin-angiotensin system (RAS) peripherally and is an agonist of the Mas receptor centrally. Activation of this receptor in the CNS stimulates various biological activities that make the Ang (1-7)/MAS axis a novel therapeutic approach for the treatment of many diseases. The related O-linked glycopeptide, Asp-Arg-Val-Tyr-Ile-His-Ser-(O-β-D-Glc)-amide (PNA5), is a biousian revision of the native peptide hormone Ang (1-7) and shows enhanced stability in vivo and greater levels of brain penetration. We have synthesized the native Ang (1-7) peptide and the glycopeptide, PNA5, and have formulated them for targeted respiratory delivery as inhalable dry powders. Solid phase peptide synthesis (SPPS) successfully produced Ang (1-7) and PNA5. Measurements of solubility and lipophilicity of raw Ang (1-7) and raw PNA5 using experimental and computational approaches confirmed that both the peptide and glycopeptide have high-water solubility and are amphipathic. Advanced organic solution spray drying was used to engineer the particles and produce spray-dried powders (SD) of both the peptide and the glycopeptide, as well as co-spray-dried powders (co-SD) with the non-reducing sugar and pharmaceutical excipient, trehalose. The native peptide, glycopeptide, SD, and co-SD powders were comprehensively characterized, and exhibited distinct glass transitions (Tg) consistent with the amorphous glassy state formation with Tgs that are compatible with use in vivo. The homogeneous particles displayed small sizes in the nanometer size range and low residual water content in the solid-state. Excellent aerosol dispersion performance with a human DPI device was demonstrated. In vitro human cell viability assays showed that Ang (1-7) and PNA5 are biocompatible and safe for different human respiratory and brain cells.